Means and Ends The Idea of Capital in the West, 1500-1970 - Boldizzoni, F. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Capital has dominated the imagination of Western society from the Industrial Revolution. Means and Ends offers the first comprehensive interpretation of the rise, evolution and crisis of this concept from the sixteenth century to the modern day. Based on a wealth of primary sources it offers an exciting study of intellectual and cultural history.